2020
DOI: 10.1002/ccd.28953
|View full text |Cite
|
Sign up to set email alerts
|

Superior vena cava filter placement over existing central venous lines: Is line removal necessary?

Abstract: Objectives To evaluate the technical feasibility and clinical safety of superior vena cava (SVC) filter placement over preexisting central venous lines (CVLs) in 23 patients who had upper extremity deep venous thrombosis with contraindications to anticoagulation. Methods A retrospective review of the images and electronic medical records of 23 patients from 2008 to 2018 with SVC filters placed over an existing central venous line was performed in a single tertiary medical center. Twenty‐one filters were placed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Despite increasing incidence of UEDVT with the development and use of peripherally inserted central lines, the overall incidence of UEDVT remains low, accounting for only 4% to 6% of all DVTs. 20 Placing filters in the superior vena cava (SVC) to prevent PE in patients with known UEDVT remains controversial and is considered an off-label use, as currently no FDA-approved SVC filter exists. 10,20 One comprehensive literature review of 21 publications describing SVC filter use found only a 5.6% incidence of PE in patients with UEDVT and a mortality rate from PE of 0.7%, which they concluded was not enough evidence to demonstrate significant risk of UEDVTs.…”
Section: Superior Vena Cava Placementmentioning
confidence: 99%
See 4 more Smart Citations
“…Despite increasing incidence of UEDVT with the development and use of peripherally inserted central lines, the overall incidence of UEDVT remains low, accounting for only 4% to 6% of all DVTs. 20 Placing filters in the superior vena cava (SVC) to prevent PE in patients with known UEDVT remains controversial and is considered an off-label use, as currently no FDA-approved SVC filter exists. 10,20 One comprehensive literature review of 21 publications describing SVC filter use found only a 5.6% incidence of PE in patients with UEDVT and a mortality rate from PE of 0.7%, which they concluded was not enough evidence to demonstrate significant risk of UEDVTs.…”
Section: Superior Vena Cava Placementmentioning
confidence: 99%
“…20 Placing filters in the superior vena cava (SVC) to prevent PE in patients with known UEDVT remains controversial and is considered an off-label use, as currently no FDA-approved SVC filter exists. 10,20 One comprehensive literature review of 21 publications describing SVC filter use found only a 5.6% incidence of PE in patients with UEDVT and a mortality rate from PE of 0.7%, which they concluded was not enough evidence to demonstrate significant risk of UEDVTs. 10 Another single-center 10-year retrospective review came to a similar conclusion and further identified a significant rate of complications, such as filter misplacement, SVC perforation and/or thrombosis, recurrent pneumothorax, and filter tilting.…”
Section: Superior Vena Cava Placementmentioning
confidence: 99%
See 3 more Smart Citations